Realising the potential of art-based methods in managerial learning: embodied cognition as an explanatory view of knowledge - Springborg, Claus; Ladkin, Donna (Academy of Management, 2014)
Although art-based methods are increasingly being used in management learning interventions (Taylor & Ladkin, 2009) there is little understanding about the means by which these methods foster particular learning outcomes. This conceptually-based paper addresses this concern through revisiting the philosophy of art and education (Arnheim, 1969; Dewey, 1934; Eisner, 2002; Langer, 1951) in light of recent theoretical developments in neuroscience known as embodied cognition (Niedenthal, Barsalou, Winkielman, Krauth- Gruber, & Ric, 2005; Rohrer, 2007; Wilson, 2002). We propose that embodied cognition’s recognition of the central role played by ‘simulation’ (Barsalou 1999, 2008) in learning processes offers unique insights into the mechanisms through which arts-based methods work and how they differ from (other) experiential learning interventions. This exploration leads to two propositions, a) stimulating new activation patterns in the way the brain engages with a phenomenon enables new possibilities for dealing with that phenomenon; and b) making art is a means by which those new activation patterns can be created. The paper concludes by demonstrating the power of this understanding by re-interpreting three scholarly accounts of the use of art-based methods within manager development, and suggesting implications for how such interventions can more fully realise their developmental potential.
Keywords: aesthetic-based learning; arts-based methods; embodied cognition; perceptual symbol system theory; managerial learning interventions; theory of knowledge